Peningkatan Hasil Belajar Siswa SMK 10 Nopember Jombang Melalui Pelatihan Mesin CNC Roughter - Basuki, Basuki; Rosadi, Mohammad Munib; Minto, Minto; Pramitasari, Retno Eka; Hadi, Fajar Satriya; Wati, Dian Anisa Rokhmah (Universitas Nusantara PGRI Kediri, 2024)
CNC (computerized numerical control) is which means that all movements of machine parts are moved or controlled by program commands in the form of numerical codes on a computer. CNC knowledge needs to be given from an early age in vocational high schools or vocational schools. Vocational school graduates need to master this reliable technology in order to be able to compete, because almost all industrial machines have implemented digitalization systems with the aim of efficiency. Therefore, it is necessary to provide vocational school level CNC roughter training to improve skills before entering the world of work. The service stages include preparation, implementation, evaluation and reporting stages. CNC roughter machine training is able to influence the learning outcomes of class XI students at SMK 10 November Jombang.